The engaging of early age children in environmental behavior through wayang kancil folktale - Wakhid Musthofa; Koentjoro Koentjoro (Sustinere: Journal of Environment and Sustainability, 2019)
School is a medium to solve the waste problem through clean lifestyle psychoeducation. Wayang kancil folktale uses animal characters as an alternative method to teach early age children to reduce littering behavior. This approach is applied because the animal world is close to the children's world. In addition, an interaction between children and the storyteller through folktale occurs during wayang kancil show. This study is action research which involves 14 second-year nursery student from a pre-school institution in Yogyakarta. The A-B-A experiment design puts the hypotheses of wayang kancil folktale to stimulate littering behavior at an early age to the test. Baseline, intervention, and reversal measurement was conducted consecutively for nine days which was recorded in observation sheets. Comprehension test was carried out before and after the intervention. The observation result was analyzed using visual analysis. Meanwhile, a comprehension score is rated by implemented paired sample t-test. The coefficient of reliability test of inter-rater was 0.971. Pre and post-intervention comprehension score increased rapidly (p = 0.000; < 0.01). The result proves that wayang kancil folktale was able to reduce children’s littering behavior.